HDAC3–ERα Selectively Regulates TNF-α-Induced Apoptotic Cell Death in MCF-7 Human Breast Cancer Cells via the p53 Signaling Pathway - Seung-Ho Park; Hyunhee Kim; Sungmin Kwak; Ji-Hoon Jeong; Jangho Lee; Jin-Taek Hwang; Hyo-Kyoung Choi; Kyung-Chul Choi (Cells, 2020)
Tumor necrosis factor-α (TNF-α) plays a significant role in inflammation and cancer-related apoptosis. We identified a TNF-α-mediated epigenetic mechanism of apoptotic cell death regulation in estrogen receptor-α (ERα)-positive human breast cancer cells. To assess the apoptotic effect of TNF-α, annexin V/ propidium iodide (PI) double staining, cell viability assays, and Western blotting were performed. To elucidate this mechanism, histone deacetylase (HDAC) activity assay and immunoprecipitation (IP) were conducted; the mechanism was subsequently confirmed through chromatin IP (ChIP) assays. Finally, we assessed HDAC3–ERα-mediated apoptotic cell death after TNF-α treatment in ERα-positive human breast cancer (MCF-7) cells via the transcriptional activation of p53 target genes using luciferase assay and quantitative reverse transcription PCR. The TNF-α-induced selective apoptosis in MCF-7 cells was negatively regulated by the HDAC3–ERα complex in a caspase-7-dependent manner. HDAC3 possessed a p53-binding element, thus suppressing the transcriptional activity of its target genes. In contrast, MCF-7 cell treatment with TNF-α led to dissociation of the HDAC3–ERα complex and substitution of the occupancy on the promoter by the p53–p300 complex, thus accelerating p53 target gene expression. In this process, p53 stabilization was accompanied by its acetylation. This study showed that p53-mediated apoptosis in ERα-positive human breast cancer cells was negatively regulated by HDAC3–ERα in a caspase-7-dependent manner. Therefore, these proteins have potential application in therapeutic strategies.